The Relationship Between Gestational Age, Parity, Nutritional Status with the Incidence of LBP in Pregnant Women - Alfiana Novianty Yazir; Rauly Rahmadhani; Dewi Setiawati; Jelita Inayah Sari (Fakultas Kesehatan Masyarakat, Universitas Muhammadiyah Palu, 2024)
Background: Low Back Pain (LBP) is pain that arises in the lower back of the body, including the lower spine, waist, pelvis, and can radiate to the buttocks or legs. low back pain is one of the most common pains in pregnant women with an incidence of about 60%-90%. Objective: The purpose of the study was to determine the relationship between gestational age, parity and nutritional status of pregnant women with the incidence of low back pain based on the Oswestry Disablity Index (ODI). Method: The research design used was non-experimental with a cross sectional research approach. This research was conducted at Wirahusada Medical Center Clinic Makassar 2022 and there were 95 research samples. This research data uses primary data from the results of filling out questionnaires by respondents. Data were processed using SPSS with the Chi-Square test. Result: The results showed that gestational age with low back pain had a p-value of 0.000, parity with low back pain had a p-value of 0.000, nutritional status based on upper arm circumference with low back pain had a p-value of 0.020, and nutritional status based on upper arm circumference with low back pain had a p-value of 0.000. Conclusion: The results showed that there was a relationship between gestational age, parity, and nutritional status of pregnant women with the incidence of low back pain based on the Oswestry Disability Index at the Wirahusada Medical Center Clinic Makassar 2022 with a p-value <0.05.